Factors affecting the culture of innovation in the activities of Innovative and Creative (KIK): innovation group at Pahang State Secretary Office, Kuantan / Mazri Mamat and Wan Asri Wan Ab. Aziz - Mamat, Mazri; Wan Ab. Aziz, Wan Asri (2021)
The aim of this study is to identify the factors that influence the culture of innovation in Pahang State Secretary Office, Kuantan through the activities of the Innovative and Creative Group (KIK) /Innovation. This study also intends to find the relationship between involvement and cultural factors of creativity and innovation in the Pahang State Secretary Office .Based on the study and knowledge gained from relevant literature, a conceptual framework is gradually built. The sample technique used to fulfil the study's goal was stratified random sampling .The sample size of respondents from the Pahang State Secretary's Office, Kuantan selected is 103 out of 140 total population of the Pahang State Secretary's Office consists of KIK / Innovation group. Descriptive analysis of the data collection found that the framework is dependable and delivers what it was designed for, with significant item-to-total correlations and regression analysis for the dimensions studied and a high Cronbach's alpha value. This methodology is used in this study since it is a convenient way to gather information from respondents. The information was collected using a questionnaire provided. Cronbach Alpha coefficients were used to assess reliability. There were four independent variables and one dependent variable in this study. Studies have found that change management and learning greatly influence and influence engagement and innovation culture. Research in the future should look at how a culture of innovation can be used as a driver to develop creativity and innovation in organisations.